2006
DOI: 10.1111/j.1567-1364.2006.00055.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of clinical and environmental isolates of theCryptococcus neoformansspecies complex reveals a high genetic diversity and the presence of the molecular type VGII mating type a in Colombia

Abstract: The aim of this study was to investigate the epidemiological relationships of clinical and environmental isolates of the Cryptococcus neoformans species complex in Colombia. The current study reflects data from 1987 to 2004. In Colombia serotypes A and B are most frequently recovered from patients and the environment. Of the 178 clinical isolates studied, 91.1% were of serotype A, 8.4% serotype B and 0.5% serotype C. Of the 247 environmental isolates, 44.2% were of serotype A, 42.6% serotype B and 13.2% seroty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
86
1
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 47 publications
14
86
1
4
Order By: Relevance
“…However, it is worth mentioning that this multiplex PCR has been proven to be an excellent choice for C. neoformans serotypes A and D. An important fact, is that all C. neoformans var. grubii isolates recovered were molecular type VNI and most of the C. gattii isolates were molecular type VGIII (67%), which is in agreement with other studies made in Colombia, where these molecular types had been the most prevalent within these species (12,25).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, it is worth mentioning that this multiplex PCR has been proven to be an excellent choice for C. neoformans serotypes A and D. An important fact, is that all C. neoformans var. grubii isolates recovered were molecular type VNI and most of the C. gattii isolates were molecular type VGIII (67%), which is in agreement with other studies made in Colombia, where these molecular types had been the most prevalent within these species (12,25).…”
Section: Discussionsupporting
confidence: 91%
“…gattii species complex recovered in this study was very small, this is the first report about the isolation of C. gattii serotype B from the environment in Cúcuta. This report confirms the presence of C. gattii in a terrestrial ecosystem, and although the isolate recovered was molecular type VGI, in contradistinction to the clinical isolates that have been recovered in Cúcuta, which are the majority molecular type VGII (12), the isolation of C. gattii serotype B helps us to clarify how the incidence of human cases of cryptococcosis reported in this Colombian city, could be probably due to the environmental exposure to this fungus, due to the fact that the recovering of C. gattii from the environment in Cúcuta had been only reported for serotype C isolates (11). Additionally, this suggests that it is necessary to do further studies in order to recover environmental isolates belonging to the same molecular pattern as the clinical isolates.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Cryptic same-sex reproduction enabled expansion to a new geographical niche and contributed to the ongoing production of infectious spores [20]. Serotype C strains only rarely cause human infection [21,22].…”
Section: Classification Of Cryptococcus Neoformans and C Gattiimentioning
confidence: 99%
“…Epidemiological surveys have shown that mating type α strains are most prevalent in serotype A isolates, both clinical and environmental (16), whereas in serotype B, we found that mating type a is more frequent in Colombia (17).…”
mentioning
confidence: 53%